Kepastian Hukum Prosedur Penggantian Kerugian Pemegang Hak Atas Tanah Yang Terdampak Proyek Jalan Tol - Roni Andriyanto; Dhody Ananta Rivandi W; Ismail Ismail (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Affected by a Toll Road Project. This study employs the Legal Certainty Theory of Jan Michiel Otto and the Development Law Theory of Mochtar Kusumaatmadja as its legal theories. This research employs a normative-juridical methodology in an endeavor to collect pertinent information regarding the issue at hand. The philosophical approach and the case approach are utilized in the study process. According to the findings of the study, proper and equitable compensation was provided to the rightful parties in the land acquisition process. The Compensation Procedure consists of the phases of planning, preparation, implementation, and results in submission. In the supply of compensation, every effort should be made to achieve an agreement so that those entitled receive the compensation immediately.